A Systematic Review of the Definitions, Determinants, and Clinical Outcomes of Antimicrobial De-escalation in the Intensive Care Unit. (23rd December 2015) - Tabah, Alexis; Cotta, Menino Osbert; Garnacho-Montero, Jose; Schouten, Jeroen; Roberts, Jason A.; Lipman, Jeffrey; Tacey, Mark; Timsit, Jean-François; Leone, Marc; Zahar, Jean Ralph; De Waele, Jan J.
Abstract : In this systematic review the authors found no precise definition of antimicrobial de-escalation (ADE). The association between ADE and improved outcomes is biased by common determinants such as appropriate antimicrobial therapy, the absence of multidrug-resistant bacteria, and clinical improvement. Abstract: Antimicrobial de-escalation (ADE) is a strategy to reduce the spectrum of antimicrobials and aims to prevent the emergence of bacterial resistance. We present a systematic review describing the definitions, determinants and outcomes associated with ADE. We included 2 randomized controlled trials and 12 cohort studies. There was considerable variability in the definition of ADE. It was more frequently performed in patients with broad-spectrum and/or appropriate antimicrobial therapy ( P = .05 to .002), when more agents were used ( P = .002), and in the absence of multidrug-resistant pathogens ( P < .05). Where investigated, lower or improving severity scores were consistently associated with ADE ( P = .04 to <.001). The pooled effect of ADE on mortality is protective (relative risk, 0.68; 95% confidence interval, .52–.88). Because the determinants of ADE are markers of clinical improvement and/or of lower risk of treatment failure this effect on mortality cannot be retained as evidence. None of the studies were designed to investigate the effect of ADE on antimicrobial resistance.